(untitled) (Research, Society and Development, 2020)
Analizes of methodologies that gather scientific information about students’ daily lives is important to reflection and the construction of strategies for a better understanding of contents. This article sought to value the knowledge about medicinal plants and to use them in contexts of culture and tradition in botanical education to contribute to the teaching of science, in the municipality of Paragominas, Pará, Brazil. The methodology used was action research, in which students and the teacher of the class sciences were interviewed. Thus, actions were developed that sought to promote the interdisciplinarity of the contents (photosynthesis and food chain) with the proposed theme through theoretical class and making a garden in the school environment. From the results, it was concluded that those involved were stimulated with this teaching practice, which contributed to the contextualized understanding of the botany content.